2020
DOI: 10.3233/thc-209018
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models of hypertensive disorders in pregnancy based on support vector machine algorithm

Abstract: BACKGROUND: The risk factors of hypertensive disorders in pregnancy (HDP) could be summarized into three categories: clinical epidemiological factors, hemodynamic factors and biochemical factors. OBJECTIVE: To establish models for early prediction and intervention of HDP. METHODS: This study used the three types of risk factors and support vector machine (SVM) to establish prediction models of HDP at different gestational weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The majority of the studies (n=22) were published between 2016 and 2020. AI techniques were used for predicting pregnancy disorders/complications in about 75% (n=18) of the included studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Specifically, the techniques discussed were utilized for predicting preeclampsia [5,7,9,15], preterm birth [6,13,19], gestational diabetes [8,14,21], gestational age [4,18], patient's metabolomics profile [12,20], suicidal behavior [11], uterine contractions [16], labor due date [17], and hypertensive disorder [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the studies (n=22) were published between 2016 and 2020. AI techniques were used for predicting pregnancy disorders/complications in about 75% (n=18) of the included studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Specifically, the techniques discussed were utilized for predicting preeclampsia [5,7,9,15], preterm birth [6,13,19], gestational diabetes [8,14,21], gestational age [4,18], patient's metabolomics profile [12,20], suicidal behavior [11], uterine contractions [16], labor due date [17], and hypertensive disorder [10].…”
Section: Resultsmentioning
confidence: 99%
“…AI techniques were used for predicting pregnancy disorders/complications in about 75% (n=18) of the included studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Specifically, the techniques discussed were utilized for predicting preeclampsia [5,7,9,15], preterm birth [6,13,19], gestational diabetes [8,14,21], gestational age [4,18], patient's metabolomics profile [12,20], suicidal behavior [11], uterine contractions [16], labor due date [17], and hypertensive disorder [10]. Additionally, of the 24 studies, four (n=4, 17%) employed AI techniques for treatment and management of ectopic pregnancies [22], gestational diabetes [23], late-onset preeclampsia [5], and hypertensive disorder [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, in a Korean study of over 11,000 women, Jhee et al showed that the combined application of maternal factors and common antenatal laboratory data in various machine learning algorithms resulted in improved prediction performance of PE, compared to traditional statistical models [78]. In a smaller study of Chinese women, support vector machine algorithms based on a combination of epidemiological, haemodynamic and biochemical factors were found to improve model accuracy and discrimination of HDP [80].…”
Section: Machine Learning Approachesmentioning
confidence: 99%
“…Finally, there is an emerging body of literature on the application of machine learning with gestational diabetes or hypertension as the dependent variable [71][72][73][74]. The independent variables of machine-learning studies on gestational diabetes [71,72] include age, blood pressure, body mass index, diabetes pedigree function, education (elementary, junior high school, senior high school, and university), fasting plasma glucose, gestational diabetes history, pregnancies (number), serum insulin, skin-fold thickness, and smoking.…”
Section: Recent Expansion Of Artificial Intelligence In Maternal-fetal Medicinementioning
confidence: 99%